Skin in the Game versus Skimming the Game: Governance, Share Restrictions, and Insider Flows - Ozik, Gideon; Sadka, Ronnie (Journal of Financial and Quantitative Analysis, 2015)
Abstract This paper advances the proposition that share restrictions engender potential conflicts of interest between fund managers and investors. Fund flows predict future fund returns for share-restricted funds, especially among funds with low levels of governance and funds managing insiders’ wealth, providing managers incentive to trade in advance of their clients. Some direct evidence for such managerial action is presented, using proprietary data on managerial investment in their own funds. The evidence suggests that private information about a fund, not necessarily its holdings, may constitute material information, with implications for proper fund governance and disclosure policy concerning managerial actions.